1995
DOI: 10.1177/002224299505900405
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cartoon Trade Character Recognition and Attitude toward Product Category in Young Children

Abstract: The author reviews and tests the effect of cartoon trade characters on product recognition and attitude on a sample of children three to six years of age. High levels of product and trade character recognition were found, including that of Joe Camel and the Marlboro Man with cigarettes. The recognition of select trade characters tended to increase with the age of the child. The level of recognition and favorable attitude toward the product were positively associated with age except for cigarettes. The attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 25 publications
2
41
0
5
Order By: Relevance
“…Similar results have been described in Australia (24). Given that evidence shows that spokescharacters are effective at attracting children's attention, increasing product recognition and inducing favourable attitudes toward a product (25,26), an exclusive focus on licensed characters in self‐regulatory commitments regarding marketing to children is not sufficent. Food and beverage corporations must extend their pledges to limit the use of spokescharacters in food and beverage marketing.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been described in Australia (24). Given that evidence shows that spokescharacters are effective at attracting children's attention, increasing product recognition and inducing favourable attitudes toward a product (25,26), an exclusive focus on licensed characters in self‐regulatory commitments regarding marketing to children is not sufficent. Food and beverage corporations must extend their pledges to limit the use of spokescharacters in food and beverage marketing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research had shown the relationship between the product characteristics and kids intention to consume (McNeal, 1992;Levin & Page, 2003;Mizerski, 1995;Gruner & Homburg, 2000). Kids are very concern about the product characteristics when they want to buy or consume a product (McNeal, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…5 Promotional characters are a key persuasive tool for advertisers seeking to engage children with their brand, and children 2-7 years of age are increasingly influenced by imagery and symbolism in advertising. 6,7 Promotional characters are of particular concern because, although they can have positive effects on choice of healthier foods such as fruit and vegetables, [8][9][10] they have been found predominantly to promote foods that are high in fat, salt, and sugar (HFSS). A content analysis of childtargeted TV advertising across several countries found that up to 49% of food commercials contained promotional characters, of which 79% were for HFSS foods.…”
mentioning
confidence: 99%